Keputusan Penggunaan Aplikasi Fintech PosPay : Brand Image dan Customer Experience di kota Bandung - Annisawati, Asaretkha Adjane; Rezi, Muhammad Alva; Triputranto, Bambang (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Digital wallet applications are expanding with various brands and engaging user experiences to meet the needs of an established market, particularly in terms of fast and practical payments. PT. Pos Indonesia offers a digital wallet application called Pospay. The purpose of this study is to evaluate the influence of brand image and user experience on the decision to use the Pospay application in the city of Bandung. The study sample consists of 100 users of the Pospay application. Data were collected through the distribution of questionnaires using a semantic differential scale in a quantitative approach. The data analysis technique used is associative descriptive analysis, using SPSS 25. The findings of the study indicate that brand image has a positive and significant influence on the decision to use the application, as does user experience. Additionally, brand image and user experience together have an impact on the decision to use the Pospay application